Limited Utility of Gadolinium Contrast Administration in Routine Multiple Sclerosis Surveillance. Issue 1 (4th November 2020) - Johnston, Gregory; Johnson, Thomas; Solomon, Andrew J.; Bazylewicz, Michael; Allison, James B.; Azalone, Emily; Ulano, Adam
ABSTRACT: BACKGROUND AND PURPOSE: Assess the incidence of enhancing lesions on follow‐up MRIs in patients with multiple sclerosis (MS) to determine the utility of intravenous, gadolinium‐based contrast agent (IV‐GBCA) use in routine follow‐up imaging. METHODS: We retrospectively identified head MRIs associated with an MS diagnosis acquired between January 1, 2015and January 10, 2018. Final reports were reviewed to determine the presence of (1) a new or larger lesion, (2) at least one enhancing lesion, and (3) if at least one enhancing lesion was new or larger on Fluid‐Attenuation Inversion Recovery (FLAIR). For MRIs with at least one enhancing lesion, but no new or larger enhancing lesions, reports and images of the preceding MRI were reviewed. RESULTS: A total of 1, 805 MRIs performed on 920 patients were included. 354/1, 805 (20%) MRIs reported new or enlarging lesions. 138/1, 805 (8%) MRIs reported at least one enhancing lesion. Of these, 117/138 (85%) reported at least one enhancing lesion that was new or larger. In the remaining 21 MRIs which contained an enhancing lesion but none of the enhancing lesions were reported as new or enlarging, at least one enhancing lesion was present on preceding MRI. CONCLUSIONS: Enhancing lesions are uncommon on follow‐up MRIs in MS patients. Our data suggest that new enhancing lesions are not present on a follow‐up MRI when two conditions are met: (1) preceding MRI does not demonstrate any enhancing lesions and (2) there is no interval change of the lesions on the current 3D‐T2‐FLAIR sequence compared to the preceding 3D‐T2‐FLAIR sequence. IV‐GBCA should be reserved for instances when temporal knowledge of lesion formation is needed.